KATA SIFAT DALAM BAHASA INGGRIS DAN BAHASA TABARU SUATU ANALISIS KONTRASTIF - LOBO, LONDRIK (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT This study entitled “ The Adjective in English and Tabaru Language: A Contrastive Analysis‟‟ aims at identifiying and classifiying the adjectives in English and Tabaru Language, in terms of froms types and position. The English data were collected from some English book. while the Tabaru Language data was collected from six s informants. The data was analyzed using Frank , than theory than contrasted Lado‟s theory to find out the differences adjective of both Language in terms of their types and position. The result shows that English has six types of adjectives those are determiner ( article, demonstrative adjective, possessive adjective, numeral adjective, relative and interrogative adjective, and adjective of indenfinitie quantity). And descriptive adjectives whereas Tabaru Language has those types except relative adjective in term of position. Tabaru Language doesn‟t have adjectives after in definite pronoun. Keywords: Adjective in English and Tabaru Language contrastive analysis.